Cultural Diversity and Its Impact on Workplace Collaboration and Innovation - Ahmed Raza Khan; Saira Malik; Hina Ali (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This article explores how cultural diversity within teams impacts collaboration and innovation in multinational organizations. Using case studies from various industries, the study examines both the advantages and challenges presented by diverse work environments, focusing on communication barriers, problem-solving abilities, and enhanced creativity. Findings show that while cultural diversity can foster innovation and creativity, successful collaboration relies on effective communication strategies and an inclusive work culture.